Homicidal Stab Injury Over an Extremely Rare Site: a Case Report - Dr. Bedanta Sarma (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction Stab injury is a three dimensional mechanical injury, most of which is located over the chest and abdomen. Fatal stab injury of extremity especially over anterior aspect of thigh is a rare entity. It directly causes injury to the femoral vessel if the stroke can be placed exactly over its anatomical landmark. Hence, to execute such type of site specific injury, the victim or the accused must have anatomical knowledge. Few such rare incidences have been reported till now with possibility of all the manners. Case presentation Such a victim was brought to the mortuary of tertiary care centre, Dibrugarh (Assam) on 4th March 2014 with a stab injury over anterior aspect of upper thigh by an acquaintant under the influence of alcohol. Both the victim as well as the accused was illerate and farmer by occupation. The victim became unconscious in a pool of blood and was declared dead after reaching hospital. Conclusion The uniqueness of the case is that the victim chose an extremely rare site for stabbing In spite of not having anatomical knowledge. In this paper the case has been described in the light of autopsy findings.